2019
DOI: 10.1016/j.bjorl.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus evaluation: relationship between pitch matching and loudness, visual analog scale and tinnitus handicap inventory

Abstract: There was a significant correlation between the values measured by the tinnitus handicap inventory, visual analogical scale (annoyance) and loudness matching in the evaluation of tinnitus. The selection of any one of the three evaluative methods for tinnitus investigation provides different dimensions of the tinnitus and complements the others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 34 publications
(40 reference statements)
4
12
2
11
Order By: Relevance
“…Regarding the psychoacoustic measures researched, the data from both groups did not differ and corroborate the greater occurrence of high-pitched tinnitus, as well as the region of hearing loss in the case of GI subjects (21) . Although a recent study demonstrated similar pitch perception results around the 6000Hz frequency (25) , the fact that the high frequencies were not included in the present research may justify the fact that the mean value found here, in both groups, is considered lower compared to other works, ranging from 10 to 14000Hz (26) .…”
Section: Discussioncontrasting
confidence: 56%
“…Regarding the psychoacoustic measures researched, the data from both groups did not differ and corroborate the greater occurrence of high-pitched tinnitus, as well as the region of hearing loss in the case of GI subjects (21) . Although a recent study demonstrated similar pitch perception results around the 6000Hz frequency (25) , the fact that the high frequencies were not included in the present research may justify the fact that the mean value found here, in both groups, is considered lower compared to other works, ranging from 10 to 14000Hz (26) .…”
Section: Discussioncontrasting
confidence: 56%
“…It is conceivable that subjective tinnitus loudness might influence some of the obtained results. Unfortunately, there is not an agreement on whether the THI score used in our work may serve as an index of subjective tinnitus loudness: some studies have shown that tinnitus loudness judgments correlate well with self-rated annoyance and THI (e.g., Newman et al, 1994; Degeest et al, 2016), other studies found no correlation between subjective tinnitus ranking or THI and matched loudness (Meikle et al, 1984; Nascimento et al, 2018). Future work is hence needed to fully clarify this issue.…”
Section: Discussionmentioning
confidence: 78%
“…It is worth noting that, in our study, we found a significant, negative correlation between the level of vitamin D and the impact of tinnitus measured with THI and VAS scales, but not with tinnitus pitch and loudness. Indeed, many studies show that the VAS scale for tinnitus loudness does not correspond to psychoacoustic measures of tinnitus loudness, and there is no correlation between THI and pitch and loudness matching measurements [ 63 , 64 ]. The reason for this discrepancy is that psychoacoustic measurements do not assess reactions to tinnitus, and self-reported tinnitus loudness is more a measure of tinnitus reactions than perception [ 65 ].…”
Section: Resultsmentioning
confidence: 99%